ANALISIS SISTEM TERMAL DITINJAU DARI PENGARUH RASIO UDARA BAHAN BAKAR SOLAR TERHADAP PRODUKSI SATURATED DAN SUPERHEATED STEAM PADA BOILER - Tahdid; Fatria; K.A. Ridwan; Salisa Fikamalati; Zenia Zal Putri (KINETIKA, 2021)
Boiler is a closed vessel used to produce steam. Steam is obtained from heating, whose source comes from the combustion of fuel in furnace. A Cross Section Double Drum Water Tube has two drums (double drum) which are placed crosswise to the heat source and tube is installed in the opposite direction to the drum, then positioned at 65o slope to reduce the force of gravity and to accelerate the evaporation process of water molecules. The fuel used in this research used diesel fuel with air to fuel ratio as a changing (dependent) variable, while 15 liters of fuel and 75 kg of boiler feed water were fixed (independent) variables. The air to fuel ratio used ranged from excess 6% to excess 22%. The calculation results showed that the furnace efficiency saturated and superheated in water tube boiler cross section tool was 69.74% and 69.25% at air to fuel ratio of excess 18% with the saturated and superheated steam pressure had reached the optimum pressure of 5 bar and the convection heat loss was obtained from furnace surface as much as 8.12% and 7.01%.